2003
DOI: 10.1038/sj.ijir.3901022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for erectile dysfuntion in primary care: results of a Korean study

Abstract: In order to assess the prevalence and associated factors for erectile dysfunction (ED) in primary care, a cross-sectional study was undertaken by questionnaire distributed to consecutive adult male attendees at 32 family practices. ED was assessed by the Korean five-item version of the International Index of Erectile Function (IIEF-5). In total, 3501 completed questionnaires were available for analysis. The prevalence of ED was severe (IIEF-5 score: 5-9) in 1.6% of cases, moderate (10-13) in 10.2%, mild (14-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
3
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 22 publications
5
63
3
5
Order By: Relevance
“…This might partly explain the lack of association between high BMI (427.0) and ED in a large-scale Korean ED study. 26 A low BMI can be an extreme end of a physiological spectrum or the result of a pathological process (such as cachexia). Since this was a population representative sample that included healthy and infirm subjects, it was hard to pinpoint whether the low BMI was attributed to or confounded by poor general health.…”
Section: Discussionmentioning
confidence: 99%
“…This might partly explain the lack of association between high BMI (427.0) and ED in a large-scale Korean ED study. 26 A low BMI can be an extreme end of a physiological spectrum or the result of a pathological process (such as cachexia). Since this was a population representative sample that included healthy and infirm subjects, it was hard to pinpoint whether the low BMI was attributed to or confounded by poor general health.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial search identified 221 articles, but only 11 cross-sectional studies [13][14][15][16][17][18][19][20][21][22] documented the adjusted OR for alcohol, another cross-sectional study 23 and a prospective cohort 24 from the same study population provided adjusted relative risks (RR), one cohort study 25 provided adjusted OR. Only the 11 cross-sectional studies that provided adjusted ORs will be included in the meta-analysis, since the other two cohort studies were of different study design, and the RR reported by the cross-sectional and cohort studies were derived with a different statistical method (Mantel-Haenszel rather than logistic regression).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption and erectile dysfunction JYW Cheng et al (95% CI, 12-22), 16% (11-23) and 15% (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) in those with o1 drink/day, 1-3 drinks/day and X4 drinks/day of alcohol consumption respectively. This incidence figure was adjusted for age, active and passive smoking, overweight, hypertension, physical activity, cholesterol, fat intake, testosterone, depression and antihypertensive medication intake.…”
Section: Cohort Study (Mmas)mentioning
confidence: 99%
“…However, the prevalence rates found in these studies have varied widely. [3][4][5][6][7][8][9][10] The first epidemiological study of male sexual behavior was published in 1948 by Kinsey et al 11 They recruited a total of 15 781 men up to 80 years of age and found a prevalence of erectile dysfunction ranging from o1% for young men to 80% in the uppermost age group. The Massachusetts Male Aging Study, a community-based observational study of a random sample of men between 40 and 70 years of age, showed a 52% overall prevalence rate for impotence.…”
Section: Introductionmentioning
confidence: 99%